Social media learning strategies, teachers' digital competencies and online learning quality: A correlational study - Widhanarto, Ghanis Putra; Prihatin, Titi; Kusumawardani, Seftia (Jurnal Inovasi Teknologi Pendidikan, 2024)
Digital competence for teachers needs special attention because learning today cannot be separated from the use of technology, so learning is of high quality. However, conditions in Indonesia show the opposite, where not all teachers have mastered digital technology. This study examines the relationship between social media-based learning strategies teachers' digital competencies and learning quality in Indonesia. The quantitative method with a correlational approach was used in this study. A total of 1001 teachers in Indonesia were the respondents. Data was obtained through questionnaires completed by the respondents. The results showed a positive relationship between social media-based learning strategies and teachers' digital competencies. A positive relationship is also seen between social media-based learning strategies and learning quality. The implication is that teachers should maximize the use of social media in learning to increase their digital competence and improve learning quality. On the other hand, schools should also provide facilities, training, and mentoring to encourage teachers to implement social media-based learning strategies.